Fernandes (Distillers) Ltd., Rum Distillers, Blenders and Bottlers, Laventille, Trinidad, W.I. - Porter (My University, 2010)
Photo showing an aerial view of the 50 acre plant of Fernandes Distillery at Laventille, Trinidad, W.I. No. 90735.
Colour: Green, Red and Brown Hues; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rum industry--Trinidad and Tobago; Distilleries--Trinidad and Tobago